Power Efficient and Workload Aware Scheduling in Cloud - J. Assudani, Purshottam; Abimanna, Satheesh (International Journal of Engineering and Technology, 2018)
The area of cloud computing is dynamic and versatile. Its arms are open for doing the research in every aspect, whether it is scheduling or provisioning. Furthermore, the research in both the aspects includes energy efficiency, profit maximization and cost minimization for cloud provider, as well as efficient and effective scheduling of resources to workloads. Also it is important to maintain QoS for the customer without violating the SLA. The aim of cloud supplier is to provide maximum utilization of resources with increased profit, while also reducing power and cost. The user demands high throughput and minimal response time. Allocating proper resources based on the workload with low energy costs to fully utilize the resources is the objective of cloud. The service requests are generated by various users in cloud. Hence energy efficient scheduling of resources according to workload is required for better performance of system and less operative cost. This paper gives a review on workload aware and power aware scheduling in cloud..Â Â